The implication of income smoothing in the Indonesian manufacturing industry among political cost as a moderating variable - Aprilyani, Vanesa; Mashuri, Ayunita Ajengtiyas Saputri (PT WIM Solusi Prima, 2025)
Introduction: This research aims to empirically examine the effect of cash holding, bonus plan, tax planning, and political cost moderation on income smoothing as well as examine the profitability as a control variable. This research is quantitative research using secondary data. The objects of this research are manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. Methods: The methods for selecting sample criteria used purposive sampling and the sample in this research was 79 companies or 237 data samples. Hypothesis testing in this research uses multiple linear regression analysis. Results: The results of this research show that based on model 1, cash holding, bonus plan and tax planning do not have a positive effect on the practice of income smoothing. Based on model 2, the results show that: (1) cash holding and tax planning does not have a positive effect on the practice of income smoothing; (2) bonus plan has a positive effect on the practice of income smoothing; (3) Political costs cannot weaken the influence of cash holding and tax planning on the practice of income smoothing; (4) Political costs can weaken the influence of bonus plan on the practice of income smoothing.